International Trade Economic Analysis for Indian Agriculture during WTO Regime: Effects on Production, Exports, Imports and Poverty - Dastagiri, M.B.; Rao, Ch. Srinivasa; Mishra, Sweta; Bhavigna, L. (European Journal of Applied Sciences, 2021)
The law of comparative advantage is the cornerstone of international trade. Economic growth, agriculture, poverty reduction and trade have a very complicated relationship. Trade analysis helps any country to discover profitable opportunities; hence the study has undertaken with these objectives. To analyze agricultural trade growth, responsiveness, stability and estimate the effects on production, exports, imports and poverty and suggest polices for boosting Trade. The major agricultural commodities from 1990-91 to 2015-16 were selected. Estimated CAGR, Instability Index, Export import price elasticity’s and regression. During the period 1990-91 to 2015-16, wheat export price and rice import price growth rates were found to be more than other cereals. The imports price growth rate of all pulses were more than exports price growth rates indicating India is importing at higher prices. Among the oilseeds crops, mustard import price (11.05 %) and sunflower export price (7.85 %) growth rates are more. The export import quantity growth rate of all cereals, pulses, and oilseeds were found to be positive except rice imports, wheat exports and soybean imports which were negative. Export import prices of all cereals (except maize) and all pulses were found to be unstable. Import price of all oilseed crops were found to be stable (except mustard and sesamum). The study found that among cereals, pulses and oilseeds, rice (1.24 %), peas (2.36 %) and mustard (0.97 %) have high export elasticities indicating these crops highly responsive to change in international prices. The effect of trade on poverty shows that, production for cereals and pulses, import price for pulses and oilseeds, export price for all the 3 groups have adverse impact on Poverty. Only for oilseeds, production and trade balance have positive and significant effect on poverty. The effect of trade on poverty shows that, export price on all cereals, pulses, oilseeds have adverse impact on poverty. Only for oilseeds, production and trade balance have positive and significant effect on poverty. Thus import prices of cereals, quantity of imports for pulses and export prices of cereals, pulses and oilseeds need to be thoroughly examined and pre-requisite actions as well as policy measures are required. The study advocates that India should design self-reliance policies in pulse production as India is importing pulses at higher prices. India also should design new stable foreign price policy for cereals and pulses as export import prices of all cereals and all pulses were found to be unstable.